THE EXPERIMENTAL INVESTIGATION OF THE EFFECTIVENESS OF TOXIC HEPATITIS TREATMENT BY PLATELET-RICH PLASMA - Холодкова, О.Л.; Горчаг, Д.М.; Перепелюк, М.М.; Топорова, О.К.; Тірон, О.І. (World of Medicine and Biology, 2014)
Introduction. Pathogenetically substantiated treatment of toxic hepatitis requires elucidation of molecular mechanisms of fibrogenesis basic regulation, which involved growth factors and other soluble regulatory factors and their intercellular signaling pathways. At the same time, promising method of the structural integrity and functional activity of affected organs restoration is platelet-rich plasma (PRP). Based on the above objective of our work was to investigate the efficiency of PRP for the liver tissue regeneration in toxic hepatitis condition. Materials and methods. The experiment was carried out on Wistar rats, divided into 3 groups: I - animals with induced toxic hepatitis, II - animals with induced toxic hepatitis and after correction by PRP, III - animals with induced toxic hepatitis and after administration of saline at the same time and in the same doses as the PRP, a separate group of animals served as intact control. Toxic liver affection was modeled by oral administration of 50 % carbon tetrachloride oil solution within two months. Correction of toxic hepatitis was performed by introducing PRP, which received using the machine, Smart Prep (Harvester corp). PRP was injected into liver tissue twice. The determination of blood cytokines IL-4, IL-10, IL-2, IL-6 by ELISA was performed. The animals were taken out of the experiment at 2, 4 and 6 weeks after the last injection.Results and discussion. Effect of carbon tetrachloride causes inflammation in the liver, what confirmed morphologically. Consequently, ongoing proliferation of connective tissue during at least 6 weeks was detected. At the same time the animals after administration of PRP manifested significant increase of newly formed blood vessels, stored beam structure of liver lobules, and at the end of observation - increased number of binuclear hepatocytes and sinusoidal cells.In the I group of animals after 2 weeks a slight increase in the content of pro-inflammatory cytokines IL-2, IL-6 was noted compared to the intact animal group. The content of anti-inflammatory cytokines was at the same level as in the intact animal. At the same time in the II group of animals after PRP correction was determined the increased content of IL-2, IL-6 and slight growth of the IL-4 and IL-10 amount. This indicates an active process of immune response to the negative influence to minimize damage of cells for faster regeneration in a short time. In this group, after 4 weeks of experiment the contents of pro-inflammatory and anti-inflammatory cytokines were equal to those in intact animals due to the inhibition of the immune response after PRP administration. At the same time, in the animals of the I group both at 4 and 6 weeks of the experiment high levels of pro-inflammatory cytokines were stored; a very moderate increase in the content of anti-inflammatory cytokines was observed what indicates a chronic process of inflammation.PRP contains a high concentration of platelets, which are the source of a significant number of cytokines: epithelial growth factor from platelets, fibroblast growth factor, insulin-like growth factor, vascular endothelial growth factor etc. This situation contributes to cell growth and differentiation, the formation and growth of blood vessels, collagen synthesis, fibroblast proliferation, neoangiogenesis and regeneration of liver tissue after toxic injury. The fact that platelets induce migration and adhesion of stem and progenitor cells to sites of angiogenesis may explain the stimulation of proliferation and differentiation of cells into mature endothelial precursors.Thus, one can conclude that the use of PRP helps to reduce the amount of connective tissue and the number of collagen fibers in the areas of hepatocyte death; PRP administration leads to rapid regeneration of liver that is an alternative method of treatment of experimental toxic liver damage.
Keywords: toxic hepatitis; platelet-rich plasma; experiment